Low Vision Student Errors in Solving Area and Circumference of Plane Figures Problems and Its Alternative Solutions - Firstian Angger Aprilio; Rooselyna Ekawati (Program Studi S1 Matematika UNESA, 2022)
Mathematics uses a lot of visual representations, one of which is geometry. In capturing mathematical information, visual sensing plays a very important role. This has an impact on low vision students in understanding and mastering the material. This study is interested to describe errors experienced by a low vision student in solving the problem of determining the area and circumference of plane figures and its alternative solutions. This research is an intrinsic case study research with a qualitative approach. The research subject was one low vision student with normal cognitive development. Data analysis to determine student errors is described using Newman's Error Analysis. The results showed that students did not have difficulty in reading, but experienced major errors in determining the completion steps for a problem (Transformation Errors). Errors in understanding the context (Comprehension Errors) problems often occur when students are faced with complex problems. Other errors occur in the calculation (Process Skill Errors) and writing the final result (Encoding Errors). This research can be an evaluation for teachers in planning mathematics learning activities using appropriate and varied learning methods and media.